Identification of resistant sources against wilt disease in castor (Ricinus communis L.): Identification of resistant sources against wilt disease in castor (Ricinus communis L.) - V DIVYA RANI; K SADAIAH; G MADHURI; N NALINI; G NEELIMA; M SUJATHA; M SANTHA LAKSHMI PRASAD; JAWAHAR LAL (Journal of Oilseeds Research, 2023)
An experiment was carried out under wilt sick plot at Regional Agricultural Research Station, Palem during kharif, 2019 to identify the potential sources of resistance against wilt disease in castor. A total of 99 germplasm accessions were screened under sick plot conditions. Observations were recorded as per cent wilt incidence periodically at thirty days interval up to 150 days in each germplasm accession. The national checks viz., JI-35 & 48-1 were used as susceptible and resistant checks respectively and were sown after every five test entries. Among the accessions, nine entries have shown immune reaction to wilt disease and 48 accessions were recorded less than 20% wilt incidence and the range of wilt incidence in the remaining accessions was 21.4 to 75 %. The wilt incidence in susceptible (JI-35) and resistant (48-1) checks were 100% and 0% respectively.